HUBUNGAN PERAN ORANGTUA DENGAN PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA DI SMP NEGERI 9 DI WILAYAH KERJA PUSKESMAS SELABATU KOTA SUKABUMI - Dewi Amir, Mayasyanti; Naimah, Siti (Jurnal Kesehatan An-Nuur, 2025)
The role of parents is very important in educating or informing her child about menstruation, the mother has an important and central position for the growth and development of her child, especially her daughter in terms of menstruation. The aim is to find out the relationship between the role of parents and personal hygiene during menstruation in adolescents at SMP Negeri 9 Sukabumi City. The role of parents as role models, role models, motivators and mentors can be realized if it is done by parents in terms of the child's personal formation. Personal hygiene is an action to maintain the cleanliness and health of a person. The design of this study was correlational with a cross sectional approach. The population of this study were teenagers in SMP Negeri 9 Sukabumi City with a sample of 171 teenagers who were taken by total sampling. Data analysis using univariate analysis with frequency distribution and percentage of each category, bivariate analysis using somer'sd test. The results of somer'sd research with (α = 0.05) obtained p value = 0.022, which means that there is a relationship between the role of parents and personal hygiene during menstruation in adolescents. There is a relationship between the role of parents and personal hygiene during menstruation in adolescents at SMP Negeri 9 Sukabumi City. It is expected that respondents can increase awareness of personal hygiene during menstruation, and parents are expected to know the importance of their child's development in maintaining health, especially during menstruation.